2016
DOI: 10.1177/0886260516628291
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cyberbullying and Suicide Ideation: The Mediating Roles of Depressive Symptoms, Perceived Burdensomeness, and Thwarted Belongingness

Abstract: Research suggests that being cyberbullied is associated with increased risk for suicide ideation; however, few studies have examined the underlying mechanisms of this relation, and fewer have examined this relation within a theory of suicide. Specifically, the interpersonal theory of suicide posits that thwarted belongingness (indicated by loneliness and a lack of reciprocal caring relationships) and perceived burdensomeness (indicated by feelings of liability and self-hatred) increase risk for suicide ideatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 37 publications
5
43
3
1
Order By: Relevance
“…Cyberbullying victimization has also been linked to suicide ideation (Mitchell et al, 2018;Nixon, 2014;Young, Subramanian, Miles, Hinnant, & Andsager, 2016). Suicide ideation occurs when an individual repeatedly thinks about, plans, and desires to commit suicide (Beck, Kovacs, & Weissman, 1979).…”
Section: Cyberbullying and Psychosocial Maladjustmentmentioning
confidence: 99%
“…Cyberbullying victimization has also been linked to suicide ideation (Mitchell et al, 2018;Nixon, 2014;Young, Subramanian, Miles, Hinnant, & Andsager, 2016). Suicide ideation occurs when an individual repeatedly thinks about, plans, and desires to commit suicide (Beck, Kovacs, & Weissman, 1979).…”
Section: Cyberbullying and Psychosocial Maladjustmentmentioning
confidence: 99%
“…At the moment, it is not possible to compare these findings to available data in Brazil, but similar mediation role of depression was observed in studies in North America that have explored cyberbullying as predictor of suicidal ideation (Mitchell et al, 2016) and attempts of suicide (Sampasa-Kanyinga, Roumeliotis, & Xu, 2014). In this last investigation, depression fully mediated the links between cyber victimization and suicide attempts.…”
Section: Resultsmentioning
confidence: 71%
“…In addition, future research is needed to establish more diverse instruments for assessing cyberbullying. Better understanding of the pathways through which cyber-bullying emerges and affects psychological wellbeing will help educational practitioners to promote optimal development in adolescents (Gámez-Guadix et al, 2013;Mitchell et al, 2016;Smith et al, 2008;Varghese & Pistole, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of US undergraduate students showed that the link between intensity of cyberbullying and suicidal ideation was mediated by depression when controlling for sexual orientation. 42 While previous studies among school-aged adolescents have shown that depression mediated the relationship between frequency of bullying and suicide attempts for traditional bullies but not for cyberbullies, and the link between cyber or traditional victimisation with suicide attempts existed only for females. 19 Similarly, the link of bullying with suicidal-ideation and self-harm disappeared for bullies but not for victims or…”
Section: Bullying Roles and Psychological Problemsmentioning
confidence: 97%